Menakar Undang-undang Pornografi dalam Perspektif Hukum Islam dan MaqÄá¹£id al-SyarÄ«Ê¿ah - Ikhsan, Muhammad; Jannah, Sa'adal; Awal Rifai (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
This article aimed to give consideration to the existence of the Pornography Law in Indonesia. This law should be appreciated as an effort to stem the flow of pornography which is supported by the fast current of technology. In this article, the Pornography Law will be viewed from a philosophical perspective on Islamic law, particularly Maqasid Syari’ah. This study employed a qualitative descriptive research method that focuses on the study of script and using a normative theological approach. The result of the study reveals that the existence of the pornography law must be appreciated because it aims to improve the morals of the nation's children. From an Islamic perspective, the Pornography Law is seen from two aspects, namely Maqashid Syari’ah as the argumentative basis and hudud and ta’zir as the basis for imposing sanctions. The implication of the research is that application of the pornography law can be maximized and is able to see things that need to be improved in it.